Interaction effects between smoking and internet gaming disorder on resting-state functional connectivity of the ventral tegmental area and hippocampus - Qiu, Xianxin; Han, Xu; Wang, Yao; Ding, Weina; Sun, Yawen; Lei, Hao; Zhou, Yan; Lin, Fuchun (Frontiers in Neuroscience, 2023)
Background Many reports have focused on cigarette smoking and internet gaming disorder (IGD), with widespread alterations of resting-state functional connectivity (rsFC) in the reward and memory circuits, respectively. Epidemiological studies have also shown high comorbidity of cigarette smoking and IGD. However, the underlying mechanisms are still unknown. Therefore, this study investigates the comorbidity and interaction effects between smoking and IGD from the rsFC perspective. Methods Resting-state functional magnetic imaging data were collected from 60 healthy controls (HC), 46 smokers, 38 IGD individuals, and 34 IGD comorbid with smoking (IGDsm) participants. Voxel-wise rsFC maps were calculated for all subjects with the ventral tegmental area, rostral hippocampus, and caudal hippocampus as regions of interest, respectively. Results Significant interaction effects between smoking and IGD were mainly involved in the reward and memory circuits; that is, the rsFC between the ventral tegmental area and right nucleus accumbens, between the rostral hippocampus and bilateral nucleus accumbens, sensorimotor areas, and left middle temporal gyrus. Specifically, in these circuits, smokers showed decreased rsFC compared to the HC group, while IGDsm showed increased rsFC compared to smokers and IGD individuals. The IGDsm and HC groups showed no significant difference. The altered rsFC also correlated with clinical measures. Conclusion These findings indicate that lower rsFC in smokers or IGD individuals increases under the effect of another type of addiction, such as smoking and IGD, but only increases to the normal state, which might explain the comorbidity and interaction between smoking and IGD from the perspective of functional circuits.